Essential Oils from Hairy Root Cultures and Field Cultivated Roots of Valerian (Valeriana sisymbriifolium) - Y Filizadeh; G Goodarzi (Institue of Medicinal Plants, ACECR, 2010)
Background: Plant cell cultivations are considered as an alternative to agricultural processes for producing valuable phytochemicals (secondary metabolites). The use of plant cell cultures has overcome several inconveniences for the production of secondary metabolites. Objective: The essential oils isolated from roots of 24-month-old field grown valerian (Valeriana sisymbriifolium) and hairy root cultures were analysed by GC and GC-mass spectrometry. Methods: Transformed root cultures of valerian were established by inoculation of sterile plantlets grown with Agrobacterium rhizogenes strain R1601. Qualitative and quantitative differences were found between the essential oils from the non-transformed roots and those from the hairy roots. Results: There are some major differences in the hairy root culture and field grown valerian essential oils especially in valeranone, valerenal, valerenyl acetate, valerenic acid and valerenol compounds. The essential oils from the plant roots were obtained in a yield of 13.2% bornyl acetate, valerenal 12.7%, -Pinene 7.50 compared with that from transformed root culture identified as kessyi alcohol (10.10%) and kessyl acetate (9.90%), as the main constituents. Conclusion: Inoculation with Agrobacterium rhizogenes strain R1601 was found to be an effective means of inducing hairy root formation on Valeriana sisymbriifolium.